Geospatial information and the intervention of the Peruvian state in areas occupied by drug traffickers - Villacorta Huapalla, Jose Antonio (2023)
This article describes and analyzes the Peruvian state's security and defense policy in relation to the expansion of the cultivation of coca, its exploitation and transportation abroad. Next, it presents quantitative budgeting data from the defense sector related to military and police operations and actions in the fight against drug trafficking and terrorism. It analyzes the work of the modern Peru SAT-1 Peruvian satellite, managed by a team of professionals from the Comisión Nacional de Investigación de Desarrollo Aeroespacial (CONIDA), which is part of the Peruvian defense sector. In relation to this commission, it presents quantitative budgeting data corresponding to the integrated and effective management of drug supply control in Peru and the improvement of military capabilities for defense and national development. The Peru SAT-1 satellite is the most modern satellite in the entire region, offering imaging services related to military operations and others of key importance to different public entities in Peru, one of which is related to the country's defense and security and the fight against illicit crops in the areas where coca plants are grown, such as the Valles de los ríos Apurímac, Ene y Mantaro (VRAEM).